Non-Teaching Staff in the Education System of Tanzania: A Review Paper on Training Practices and Service Delivery (International Journal of Scientific Research and Management (IJSRM), 2022)
The review aims at determining the perceptions of non teaching staff on training and service delivery in education system of Tanzania and to explore the needed trainings for non teaching staff in handling students in education system of Tanzania. This paper is an internet and library-oriented. The study used secondary literature review in which the documentary review applied. Also other data were collected from published articles, books, published documents, magazines, and published dissertations/thesis related to the subject matter to achieve the specific objectives highlighted. The review informs that majority of the studied schools lacked enough non-teaching staff. There is a perception that non-teaching staff are not key players in a school and are just pillars of the school functioning. Also, it was noticed that, school leaders see as if is not the priority for taking non-teaching staff for training and hence giving them less opportunities to attend training as it is done to teaching staff who sometimes attend the in-service training from different stake holders of education. It is in this regard that, leaders are not committed to maximize the opportunities for training for non-teaching staff. Even though, non-teaching staff blame that no refreshers course to make them adopt the environment of serving students. The government leaders should look on the priorities of the government and school else well when taking non-teaching staff for further training.